Perfecting of the technological process of steel castings production of machine-building nomenclature - A. A. Radchenko; V. A. Rudenko; Ju. P. Boroznjak (Литьë и металлургия)
There is shown the method of improvement of the steel castings production technology by means of development and realization of the measures on prevention of formation of the gas origin defects on the basis of using of system approach to investigation of heat-gas regime of casting into a damp sand mold.